Factors Related to the Implementation of Regional Regulation Number 3 of 2019 Concerning Non-Smoking Areas in the Capital of Konawe Islands Regency - Darmiati, Darmiati; Saafi, La Ode; Risky, Sartini (Waluya The International Science of Health Journal, 2023)
Introduction: The implementation of Regional Regulation Number 3 of 2019 concerning Non-Smoking Areas in the Konawe Islands Regency has not been maximized. There are still many people who smoke in areas that are included in non-smoking areas. The problems in this study are factors of knowledge, attitudes, facilities, and infrastructure and the provision of sanctions related to the application of the Non-Smoking Areas Regional Regulation. Method: This research is analytical research with a cross-sectional study approach. The sample of this study was 91 respondents obtained by the Lemeshow formula, data analysis with the Chi-Square test, at a confidence level of 95% (α = 0.05). Result: The results of this study concluded that there is a strong relationship between attitudes and the application of Non-Smoking Areas Bylaws (p = 0.409), there is a very strong relationship between facilities and infrastructure and the application of Non-Smoking Areas Bylaws (p = 0.505), there is a moderate relationship between sanctions and the application of the Non-Smoking Areas Bylaw (p = 0.279). Conclusion: More active efforts are needed to socialize, supervise, and enforce the Non-Smoking Areas Bylaws so that the public can know about the implementation of the Non-Smoking Areas Bylaws and make a Regent's Regulation on the implementation of the Non-Smoking Areas Regional Regulation as a technical guide in the implementation of the Non-Smoking Areas Regional Regulation in Konawe Islands Regency.